Pemulihan Hak Milik Atas Tanah Warga Urutsewu, Kebumen Dalam Perspektif Hukum Hak Asasi Manusia - Muhammad Rizqy Rosi Mahardika; Eko Riyadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
In 2005, Indonesia officially approved the International Covenant on Economic, Social and Cultural Rights through Law Number 11 of 2005. Through this ratification, the state committed to not taking land arbitrarily which could deprive its citizens of their land ownership rights. Articles 36 and 37 paragraph (1) of Law Number 39 of 1999 also state that no one can be deprived of their property rights arbitrarily and against the law and revocation of property rights is only permitted by compensating for reasoneable and immediate losses. Even though the state's commitment to protecting land ownership rights has been acknowledged, in reality there are still difficulties in providing this protection to the community. An example can be seen in the case of the Urutsewu Community in Kebumen, which experienced land confiscation by the Indonesian Army. This research focuses on the state's restoration of land ownership rights to land arbitrarily confiscated by the Indonesian Army in the Urutsewu community. In its analysis, this research uses empirical legal research methods with a sociological approach. The sociological approach emphasizes the relationship between legal principles and norms and their implementation in empirical reality in the field and the legislative approach examines all laws and regulations related the legal issue being studied. This analysis is also applied to the reality of society which is the subject of discussion, taking into account social aspects in understanding the problem. The results of this research indicate that there has been no government effort to grant the Urutsewu community the right to recover land confiscated by the Indonesian Army.